Computer vision–assisted dietary assessment through mobile phones in female youth in urban Ghana: Validity against weighed records and comparison with 24-h recalls - Gelli, Aulo; Nwabuikwu, Odiche; Bannerman, Boateng; Ador, Gabriel; Atadze, Vicentia; Asante, Millicent; Bempong, Silas; McCloskey, Peter; Nguyen, Phuong Hong; Hughes, David; Folson, Gloria (Elsevier, 2024)
Background Gaps persist in the data on diets and on the validity of dietary assessment methods in youth in low-income and middle-income countries (LMICs) due to costs constraints. Although computer vision–assisted dietary assessment tools have been proposed, limited evidence exists on their validity in LMICs.